Country Portfolios - Kraay, Aart; Loayza, Norman; Servén, Luis; Ventura, Jaume (World Bank, Washington, D.C., 2013)
Capital flows to developing countries are small and take mostly the form of loans rather than direct foreign investment. We build a simple model of North-South capital flows that highlights the interplay between diminishing returns, production risk and sovereign risk. This model generates a set of country portfolios and a world distribution of capital stocks that resemble those in the data.